Atypical presentation of left atrial myxoma: a case report - Mujtaba Azhar Siddiqui; Muhammad Ismail Ibrahim; Muhammad Salih; Muneeba Khan; Muhammad Tariq Farman (Journal of the Pakistan Medical Association, 2024)
Atrial Myxoma is the most common primary benign tumour of the heart, commonly found in the left atrium. It typically presents in young females with characteristic features such as, constitutional symptoms, chest pain, and cardiac murmurs. However, atypical presentations can occur; causing a diagnostic challenge. This case report describes a 75-year-old male who visited the cardiology outpatient department (Name of the hospital with city) on 18th April, 2023 with a left-sided atrial myxoma in late adulthood without typical features including constitutional symptoms, chest pain, syncope, dizziness, digital clubbing or neurologic findings. Further discussed are the diagnostic techniques used to find the tumour and the treatment strategy. This case report highlights the need for cardiologists to consider Atrial Myxoma as a potential diagnosis, even in the absence of typical symptoms, in elderly male population. Keywords: Atrial Myxoma, Intracardiac tumour, Myxoma, Myxoma Resection.